Identification of a sequence required for efficient packaging of human immunodeficiency virus type 1 RNA into virions. - Lever, A (1989)
Sequences required for efficient packaging of human immunodeficiency virus type 1 (HIV-1) genome RNA into virus particles were identified. Deletion of 19 base pairs between the 5' long terminal repeat and the gag gene initiation codon of HIV-1 resulted in a virus markedly attenuated for replication in human T lymphocytes. The mutant virus was characterized by nearly wild-type ability to encode viral proteins and to produce virion particles. The mutant virions exhibited a significant reduction in the content of HIV-1-specific RNA. These results identify an important component of the HIV-1 packaging signal.